2005
DOI: 10.1158/0008-5472.can-04-2782
|View full text |Cite
|
Sign up to set email alerts
|

Additive Antitumor Effect of Aromatase Inhibitor Letrozole and Antiestrogen Fulvestrant in a Postmenopausal Breast Cancer Model

Abstract: Blocking estrogen receptors with antiestrogens and blocking estrogen synthesis with aromatase inhibitors are two strategies currently being used for reducing the effect of estrogen in postmenopausal estrogen receptor-positive breast cancer patients. To optimize these treatment strategies, we have investigated whether tumor progression can be delayed by combining the pure antiestrogen fulvestrant with the nonsteroidal aromatase inhibitor letrozole. These studies were done in ovariectomized, athymic mice bearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 20 publications
3
75
0
Order By: Relevance
“…However, overall tumor growth rate may vary between experiments. In this study, the tumors had initially regressed during treatment with letrozole (30) but grew back more slowly than in other reported investigations (32,36) and had doubled after 32 weeks of treatment. Several mice were sacrificed during the course of the treatment for tumor analysis on weeks 4, 28, and 56.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…However, overall tumor growth rate may vary between experiments. In this study, the tumors had initially regressed during treatment with letrozole (30) but grew back more slowly than in other reported investigations (32,36) and had doubled after 32 weeks of treatment. Several mice were sacrificed during the course of the treatment for tumor analysis on weeks 4, 28, and 56.…”
Section: Discussionsupporting
confidence: 40%
“…The mixed-effect model is a powerful and flexible way to analyze unbalanced longitudinal data (31). Linear models that incorporate fixed effects (entire population) and random effects (individuals drawn at random from a population) are mixed effects models (31) and were used for our previously published studies (32,33). This approach allows an exponential variable controlling the rate of growth to be estimated for each of these treatment groups, with the random effects being estimated for each subject in a group (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, VN14-1 was efficacious in preventing the formation of MCF-7Ca tumours (Figure 10). We also observed that VN/14-1 treatment caused significant reduction in uterine wet weight (data not shown), which indicates that VN/14-1 can effectively block the uterotropic activity of oestrogens produced by peripheral aromatisation of androstenedione (Goss et al, 2000;Jelovac et al, 2005).…”
Section: Effects Of Vn/14-1 Compared With Clinical Ais On Growth Of Mmentioning
confidence: 64%
“…To investigate the mechanisms of resistance to aromatase inhibitors, one approach is to use the xenograft model with tumors of human breast cancer MCF-7Ca cells stably transfected with aromatase [142,143] (Figure 7). Mice were treated with letrozole until tumors eventually began to grow.…”
Section: Drug Resistance To Antihormonesmentioning
confidence: 99%